Pengaruh Kualitas Layanan dan Diferensiasi Produk Terhadap Keputusan Pembelian di Toko Alat Kesehatan Sapta Medika Lumajang - Aulia Musfirotur Rokhim; Tri Yulistyawati Evelina; Achmad Zaini (Indo Publishing, 2025)
The health industry is a growing sector because many people need the provision of medical devices. Lumajang Regency has great potential in developing medical device distributors, supported by infrastructure growth and the increasing need for quality medical services. The purpose of this study is to analyze the effect of service quality and product differentiation on purchasing decisions at the Sapta Medika Lumajang Health Equipment Store. This research was quantitative research with variables of service quality, product differentiation and purchasing decisions. The data collection was done through observation, interviews and questionnaires using Google Form. Using purposive sampling technique, 100 consumer respondents were obtained at the Sapta Medika Lumajang Health Equipment Store. The data analysis used validity test, reliability test, descriptive analysis, classical assumption test and hypothesis test. The results of the analysis showed that service quality partially had a positive and significant effect on purchase decisions, product differentiation partially had a positive and significant effect on purchase decisions, service quality and product differentiation simultaneously had a positive and significant effect on purchase decisions. It is concluded that the service quality and product differentiation variable have an influence on purchase decisions. Thus, the Sapta Medika Lumajang Health Equipment Store is expected to continue improving the quality of service and provide information on the advantages of product differentiation. Both of these are expected to influence consumers to make purchasing decisions and strengthen business continuity in the long term.